Service Marketing Mix and Customer Satisfaction Japanese Aesthetic Salon Sun Lumiere - Budi Suryowati; Rohanita Rohanita (Greenation Research & Yayasan Global Resarch National, 2024)
This study aims to determine the influence of the 7 P's of service marketing mix elements (Product, Price, Promotion, Place, People, Process, and Physical Evidence) on customer satisfaction of Japanese Aesthetic Salon Sun Lumiere. A sample of 100 respondents was obtained using the Isaac and Michael formula using non-probability sampling techniques, by distributing questionnaires to obtain the data. The data analysis method uses Structural Equation Modeling- Partial Least Square (SEM- PLS) with the help of SmartPLS 4.0 software. The results of the study showed that the elements of product, price, place, promotion, people had an effect on customer satisfaction and the process and physical evidence had no effect on customer satisfaction of Japanese Aesthetic Salon Sun Lumiere. These findings imply that Japanese Aesthetic Salon Sun Lumiere should prioritize improving the quality of products and services, setting competitive prices, executing effective promotional strategies, choosing strategic locations, and improving employee quality to achieve higher customer satisfaction. While internal processes and physical evidence remain important, the main focus should remain on the elements that directly affect the customer experience and satisfaction